Screening of mango (Mangifera indica) germplasm for identification of sources resistant to mango malformation - Retracted - USHA, K; SINGH, OM PRAKASH; YADAV, ASHOK; G, NAYAN DEEPAK; B, SINGH; K, SHARMA D (The Indian Journal of Agricultural Sciences, 2019)
The study was carried out on 72 mango (Mangifera indica L.) cultivars and 107 mango F1 hybrids to group them based on degree of resistance to malformation during the period 2015-17. Intensity of malformation varied significantly among the mango cultivars and F1 hybrids under study. Out of 72 mango cultivars and 107 F1 hybrids studied, only three cultivars namely Bhadauran, Ilaichi and Arka Nilanchal were found to be completely free from the mango malformation disease (0%) and were categorised as resistant. Minimum disease incidence (<10%) was recorded in 11 mango cultivars, one mango species and in eight mango F1 hybrids, viz. H-2-6, H-2-14, H-3-6, H-4- 10, H-5-14, H-8-4, H-8-2. and H-8-11 and were categorized as tolerant. Twelve mango cultivars and 21 mango F1 hybrids were moderately susceptible (10-20%), while another 27 cultivars and 43 F1 hybrids were susceptible (20- 50%). The highest incidence of floral malformation intensity was recorded in 13 cultivars and 32 F1 hybrids which were categorized as highly susceptible (>50%) to mango malformation. The resistant and tolerant cultivars and F1 hybrids observed in the current study can be used as parents in future breeding programmes for developing a variety resistant to mango malformation.